Conservation agriculture for a climate-resilient and sustainable upland agriculture: A success story from a seventeen-year local program in northern Vietnam - Bui, Le Vinh; Nguyen, Hai Nui; Nguyen, Tuan Cuong; Nguyen, Duc Trung; Trieu, Hong Lua; Doan, Thanh Thuy; Nguyen, Duc Tung; Vu, Thanh Bien; Nguyen, Thu Ha (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The brief elaborates on the lessons learned from an impact assessment of a local seventeen-year initiative on cassava-based soil conservation measure on sloping land as a climate-smart agriculture practice in Van Yen District, Yen Bai Province, Vietnam. Focusing on the economic, environmental, and social benefits, the recommendations push for institutional level strategies on how this success story can be replicated in areas with similar biophysical and socio-economic conditions.